The relationship between incentives and employee performance: a study of the administrative staff of UiTM Dungun / Amalina Che Makhtar ... [et al.] - Che Makhtar, Amalina; Md Tahir, Jamilah; Maliki, Normarhasmizee; Hussain, Shaidatul Najihah (2009)
Incentive can be defined in generalized as the something that tends to motivate someone to greater effort. Employee will be offered the reward to motivate them to increase their performance or productivity. The study focus on the effect of the incentives toward the employees ’performance. The incentives consist of pay increase, rewards, and promotion. The staff performance will be measure by the staff productivity. The finding of this research about the incentive given will more influence to the employee through the promotion. It will improve the productivity of works. It is because the promotion in the UiTM is very powerful to conduct employee involvement in their activities. The data collected through the sending questionnaires to the employees